2022
DOI: 10.3389/fnmol.2022.911476
|View full text |Cite
|
Sign up to set email alerts
|

Secondary damage and neuroinflammation in the spinal dorsal horn mediate post-thalamic hemorrhagic stroke pain hypersensitivity: SDF1-CXCR4 signaling mediation

Abstract: Central post-stroke pain (CPSP) is an intractable neuropathic pain, which can be caused by primary lesion of central somatosensory system. It is also a common sequelae of the thalamic hemorrhagic stroke (THS). So far, the underlying mechanisms of CPSP remain largely unknown. Our previous studies have demonstrated that SDF1-CXCR4 signaling in the hemorrhagic region contributes to the maintenance of the THS pain hypersensitivity via mediation of the thalamic neuroinflammation. But whether the spinal dorsal horn,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Although there is no direct clinical evidence suggesting secondary injury to the spinal cord in patients with CPSP, animal studies using rats and monkeys have demonstrated that stroke can cause secondary nonischemic injury not only at the infarction site but also in the distal spinal cord. 15 , 16 Secondary spinal cord injury was mainly characterized by detectable neuronal degeneration and loss in the dorsal horn of the spinal cord and associated neuroinflammatory changes. 16 The inflammatory response in the spinal cord was mainly associated with stromal cell-derived factor 1 (SDF-1), high-mobility group box-1 (HMGB1), and NOS signaling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is no direct clinical evidence suggesting secondary injury to the spinal cord in patients with CPSP, animal studies using rats and monkeys have demonstrated that stroke can cause secondary nonischemic injury not only at the infarction site but also in the distal spinal cord. 15 , 16 Secondary spinal cord injury was mainly characterized by detectable neuronal degeneration and loss in the dorsal horn of the spinal cord and associated neuroinflammatory changes. 16 The inflammatory response in the spinal cord was mainly associated with stromal cell-derived factor 1 (SDF-1), high-mobility group box-1 (HMGB1), and NOS signaling.…”
Section: Resultsmentioning
confidence: 99%
“… 15 , 16 Secondary spinal cord injury was mainly characterized by detectable neuronal degeneration and loss in the dorsal horn of the spinal cord and associated neuroinflammatory changes. 16 The inflammatory response in the spinal cord was mainly associated with stromal cell-derived factor 1 (SDF-1), high-mobility group box-1 (HMGB1), and NOS signaling. After a stroke, the glial cells in the spinal cord are activated.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, an increasing number of investigators have devoted to microglia and pain research in the past 10 years ( Han et al, 2021 ; Yang et al, 2017 ; Zhang et al, 2018 ; Liao et al, 2020 ). Liang et al (2022) demonstrated that microglia in spinal dorsal horn tissue were significantly activated after CPSP, and inhibiting the activation of microglia was one of the effective methods for the treatment of CPSP. Our results were consistent with that, and Xe inhalation treatment effectively inhibited microglial activation, but the specific mechanism of microglia function regulation during CPSP was still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathic pain from nerve injuries other than diabetes and herpes is likely due to either peripheral nervespinal cord injury or blockage of the descending inhibitory pathways by thalamic injury, etc. [9][10][11][12]; both types of nerve injury are thought to cause neuropathic pain by stimulating the somatosensory cortex through neuronal activation in the dorsal horn of the spinal cord [13][14][15]. In my previous studies, a model of neuropathic pain with MeHg exposure has been established using rats [16,17].…”
Section: Introductionmentioning
confidence: 99%